5-Nitro-1,3-bis(prop-2-ynyl)-1H-1,3-benzimidazol-2(3H)-one - Youssef Kandri Rodi; Khalid Misbahi; Abdelkrim El-Ghayoury; Leokadiya Zorina; El Mokhtar Essassi; Lahcen El Ammari (Acta Crystallographica Section E, 2013)
The title compound, C13H9N3O3, crystallizes with two identical but differently oriented molecules in the asymmetric unit, the dihedral angle between the fused-ring systems of the two molecules being 64.39 (7)°. The two prop-2-ynyl chains are located on opposite sides of the molecule and are nearly perpendicular to the fused ring plane, as indicated by the C—N—C—C torsion angles in the range 106.0 (3)–113.4 (3)°. In the crystal, the two molecules are linked through C—H...O hydrogen bonds into dimers, which are subsequently linked by further C—H...O interactions, building a three-dimensional network.